Recent trends and future of pharmaceutical packaging technology - Zadbuke, Nityanand (Medknow Publications & Media Pvt Ltd, 2013)
The pharmaceutical packaging market is constantly advancing and has experienced annual growth of at least five percent per annum in the past few years. The market is now reckoned to be worth over $20 billion a year. As with most other packaged goods, pharmaceuticals need reliable and speedy packaging solutions that deliver a combination of product protection, quality, tamper evidence, patient comfort and security needs. Constant innovations in the pharmaceuticals themselves such as, blow fill seal (BFS) vials, anti-counterfeit measures, plasma impulse chemical vapor deposition (PICVD) coating technology, snap off ampoules, unit dose vials, two-in-one prefilled vial design, prefilled syringes and child-resistant packs have a direct impact on the packaging. The review details several of the recent pharmaceutical packaging trends that are impacting packaging industry, and offers some predictions for the future.